WAYS OF FORMING DIGITAL COMPETENCE OF HIGH SCHOOL STUDENTS IN LESSONS (Physical Culture and Sport: Scientific Perspective, 2022)
This document substantiates the need for the formation of digital competences in students and considers the main problems and challenges in education.Today's education does not require traditional teaching instructions, but the creation of a harmonious learning environment with faster assessment and greater involvement.Digital learning is a great way to reduce costs, use resources more efficiently, promote sustainability and expand the reach of students and teachers.Technologies are intertwined in many aspects of modern life and society. The digital revolution that has swept the world has begun to penetrate the field of education. The way children learn is changing rapidly and as a result technology is expected to improve the face of education, making it cheaper and more accessible.One of the main issues of the UN agenda in the field of sustainable development for the period up to 2030 is providing the younger generation with quality education. This is aimed at ensuring inclusive and equitable quality education for all.Digital technologies have become an important tool for achieving this goal. They influenced the education system. The recent COVID-19 pandemic has given even greater impetus to the use of digital technologies in education. They changed the paradigm of the entire education system. Today, digital technology is not only a provider of knowledge, but also a co-author of information, a mentor and an evaluator. Technological improvements in the field of education have made life easier for students. Instead of pen and paper, students now use a variety of software and tools to create presentations and projects. Compared to using the library stacks of books, using the iPad is relatively easier. Unlike a heavy book, surfing in an e-book is easier.Sustainable development includes social well-being that depends on education. Information technologies appeared to spread general knowledge and are the main driving force of education reforms.